(untitled) (The Peerian Journal, 2024)
The organization of the muscle allows all the fibers, and thus the fascicles, to contract and relax as a group. Contraction is stimulated by nerve impulses and triggers the movement of the muscle, while relaxation occurs when the impulse is removed and the muscle relaxes back to its natural state. This pattern of contraction and relaxation is responsible for all the movements in your body .The part of your body that moves in response to a muscle contraction depends on the location and origin point of the muscles themselves. To simplify things, we are going to focus on the skeletal muscles of the body. Most skeletal muscles are attached to bone, cartilage or connective tissue, which limits or directs their movement. For example, a muscle attached to the arm bone will only move the arm bone when stimulated. It cannot move the leg bone; therefore, its movement is determined by its points of attachment. The result of the stimulation of nervous system and contraction of muscle represent the muscle activity which measured by different system. In this project we design simple system to measure the muscle signal in different condition. The biomechanics effect we applied with our practical part that the gate cycle in several cases.The result found with phases of gate cycle in normal walking, up stairs, with lifiting weght , and abnormal person walking.